Sputter Deposition of Silver Thin Films on Pet and Laser Annealing for Flexible Strain Sensor - Cheong Kok Ming, Trisson; Ali, Ahmad Hadi (Enhanced Knowledge in Sciences and Technology, 2026)
Conductive films in flexible strain sensing is becoming increasingly important in wearable health monitoring, but the creation of high sensitivity coatings on thermo-responsive polymer substrates is largely a challenging issue. This report examines the effects of 1064 nm Nd:YAG pulsed laser annealing (PLA) of silver thin films sputter-deposited on polyethylene terephthalate (PET). SEM, AFM, and four-point probe measurements of characterization showed that laser annealing with 51.3 mJ laser energy results in annealing of continuous films with controlled annealing to form island-like nanostructures with a tunneling-dominated piezoresistive response. As a result, the optimized thin film delivered a spectacular gauge factor (GF) of about 3713 in tensile elongation and 4.5 in tensile bending, and this indicates that measured laser annealing is a viable plan to achieve the sensitivity of flexible strain sensing components.